2010
DOI: 10.1080/02643294.2010.490207
|View full text |Cite
|
Sign up to set email alerts
|

Specificity of impaired facial identity recognition in children with suspected developmental prosopagnosia

Abstract: Adults experiencing face recognition difficulties in the absence of known brain injury are described as cases of developmental prosopagnosia (DP), under the assumption that specific face recognition impairments have always been present. However, only five childhood cases of DP have been reported, and the majority had additional socio-communicative impairments consistent with an autism spectrum disorder (ASD). We tested face recognition skills of six 4- to 8-year-old children, who were suspected of having DP, a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
37
0
1

Year Published

2011
2011
2017
2017

Publication Types

Select...
6
3

Relationship

1
8

Authors

Journals

citations
Cited by 38 publications
(39 citation statements)
references
References 57 publications
1
37
0
1
Order By: Relevance
“…Our findings from children with DP are consistent with other studies that have demonstrated facespecific deficits in some children (Jones & Tranel, 2001;Wilson et al, 2010) and more general visual deficits in others (Ariel & Sadeh, 1996;Brunsdon et al, 2006;McConachie, 1976;Wilson et al, 2010). In adults, findings across studies show a similar distribution of face-specific versus general visual deficits.…”
Section: Discussionsupporting
confidence: 93%
See 1 more Smart Citation
“…Our findings from children with DP are consistent with other studies that have demonstrated facespecific deficits in some children (Jones & Tranel, 2001;Wilson et al, 2010) and more general visual deficits in others (Ariel & Sadeh, 1996;Brunsdon et al, 2006;McConachie, 1976;Wilson et al, 2010). In adults, findings across studies show a similar distribution of face-specific versus general visual deficits.…”
Section: Discussionsupporting
confidence: 93%
“…Normal for Naming, "poor" for Description of Use, but this was attributed to unfamiliarity with the objects. Wilson et al (2010) A (8M) N (7M) P (5M) 1 (A) 2 (N and P) Sequential shoe matching task. "A" performed normally on the object task, but also on the matched face task.…”
Section: Testsmentioning
confidence: 99%
“…Nevertheless both AL and K (Schmalzl et al, 2008) reported improved recognition of the trained individuals in everyday life, and the gains were maintained at 3-month and 4-week follow-ups, respectively. K was also described in Wilson et al (2010) when she was 7.5 years old, and continued maintenance of the gains was reported (but note that the authors suggest K may be on the autism spectrum). These observations suggest that in DP compensatory training may be rapid, suitable for adults and young children, suitable for individuals with perceptual impairments, and the gains may translate to everyday life (but only for trained faces) and be maintained.…”
Section: Further Considerations Of Intervention Programmesmentioning
confidence: 65%
“…Potential heterogeneity within this diagnosis was also underscored by a report that some patients referred for face recognition problems had autistic spectrum disorders or broader problems with object recognition [27]. Autistic traits likely cannot be attributed to a primary prosopagnosic deficit, as a questionnaire study of 10 patients with developmental prosopagnosia found only one showing social impairments [28].…”
Section: Key Pointsmentioning
confidence: 96%